Investigating the Spectral Nature of Gigahertz-peaked Spectra Pulsar Candidates - K. Rożko; J. Kijak; R. Basu; P. Dabhade; W. Lewandowski (The Astrophysical Journal)
We report the measurements of low radio frequency spectra of 14 gigahertz-peaked spectra (GPS) pulsar candidates, between 300 and 700 MHz, using the upgraded Giant Metrewave Radio Telescope. Combining newly collected measurements with archival results, the spectral nature of each pulsar was examined using four different physical models: simple power law, broken power law, low-frequency turnover power law, and free–free thermal absorption. Based on this analysis, we confirm the GPS nature of five pulsars, three of them being new detections. In addition, one pulsar can be classified as having a broken power law spectrum, and we found the typical power-law spectra in four other cases. In the remaining four pulsars, the spectra showed tendencies of low-frequency turnover that require further investigations at lower frequency ranges. These results demonstrate the effectiveness of wideband measurements at low frequencies, below 1 GHz, in characterizing the spectral nature in pulsars. Our results also underline the need for more systematic theoretical studies to refine existing models and better interpret pulsar emission properties.